2008
DOI: 10.1002/ajim.20594
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal respiratory health study of the wood processing industry

Abstract: Exposure to WS was not associated with significant adverse effects. Respirable RPM was associated with an obstructive effect in the milling facility, and respirable RPM was also associated with a restrictive effect in the sawmill-planing plywood facility. Finally, this study does not exclude the possibility that other exposures common to this industry can cause respiratory effects, only that none were noted in this population for wood solids for the exposure levels and durations studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…Industry-or occupation-specific studies of organic/ biological dust Of the industry-or occupation-specific studies of organic/ biological dust exposure and COPD (table 3), nine (72)(73)(74)(75)(76)(77)(78)(79)(80) were cross-sectional and ten (81)(82)(83)(84)(85)(86)(87)(88)(89)(90) longitudinal with follow up-time between 1-20 years. A majority of the studies came from Europe (72-77, 79, 80, 85, 86, 88) and the US (82,83,89,90), with two each from China (81,84) and South Africa (78,87).…”
Section: Population-based Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Industry-or occupation-specific studies of organic/ biological dust Of the industry-or occupation-specific studies of organic/ biological dust exposure and COPD (table 3), nine (72)(73)(74)(75)(76)(77)(78)(79)(80) were cross-sectional and ten (81)(82)(83)(84)(85)(86)(87)(88)(89)(90) longitudinal with follow up-time between 1-20 years. A majority of the studies came from Europe (72-77, 79, 80, 85, 86, 88) and the US (82,83,89,90), with two each from China (81,84) and South Africa (78,87).…”
Section: Population-based Studiesmentioning
confidence: 99%
“…A majority of the studies came from Europe (72-77, 79, 80, 85, 86, 88) and the US (82,83,89,90), with two each from China (81,84) and South Africa (78,87). The studies comprised a total of 16 856 subjects with exposures of cotton, flax, jute, farming, grain, wood, paper, and rubber.…”
Section: Population-based Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, not all studies agree. A recent US study has shown fewer or no symptoms from typical exposures (Glindmeyer et al 2008). Other studies have addressed the relationship between exposure to wood dust and skin pathologies (Innocenti & Del Monaco 1980) or asthma (Hessel et al 1995, Malo et al 1995.…”
Section: Introductionmentioning
confidence: 99%